DECISION SUPPORT SYSTEM FOR SELECTING BOARDING HOUSES FOR STUDENTS IN GRESIK USING THE SAW (SIMPLE ADDITIVE WEIGHTING) METHOD - Rizki Marthanugraha (CV. Denasya Smart Publisher, 2024)
Boarding houses or commonly called kos are one of the places that provide accommodation services or temporary residences consisting of several rooms where each room has facilities that have been provided by the boarding house owner. For students who study far from their hometown, of course they need a boarding house. In the process of selecting a boarding house, students studying in Gresik often experience difficulties and obstacles in selecting the boarding house because there are several criteria and factors that must be met such as location, price, facilities, and also security. To overcome the above problems, a system is needed to help students in Gresik as recommendations and also find information about boarding houses in Gresik. Therefore, a method was chosen from several existing methods, namely the Simple Additive Weighting (SAW) method. This method will later produce the largest value that will be selected as the best alternative by taking into account the existing criteria.